Remembering K. S. Krishnan (1946–2014). (March 2015) - Rikhy, Richa; Kumar, Vimlesh; Basole, Amit; Sanyal, Subhabrata
Abstract Dr. K. S. Krishnan was on the faculty of the Division of Biological Sciences at the Tata Institute of Fundamental Research (TIFR) in Mumbai, India, and later emeritus professor at the National Center for Biological Sciences (NCBS) in Bangalore, India. His research using fruit flies has contributed richly to our understanding of synaptic function and mechanisms of anesthetic action. Dr. Krishnan passed away suddenly of a heart attack on the 24th of May, 2014. Below a few of his students fondly recall how it was to work in his group.